Risk Management and Insurance Practices in Protecting the GCC Economies: Impact of Climate Change - Saad Darwish (European Scientific Journal, ESJ, 2018)
Climate change can extremely influence the progress of the Gulf Cooperation Council (GCC) nations by aggravating the burden on these states, hence, preventing them from accomplishing their economic progression. The extreme hotness and abridged precipitation will aggravate the water shortage and upsurge the occurrence of droughts. This would unfavorably influence the food production and deteriorate the present condition of food security and other related issues. The GCC area is anticipated to have more unembellished effects of Sea Level Upsurge than any other state. The current global warming has the potential of putting 6-25 million people and vital economic activities to coastal flooding. The area is one of the highly built-up states of the world. Climate change is one of the biggest challenges that humanity is facing, as it is not only a threat on biodiversity and food security, but is also impeding economic performance and growth. It is worth saying that climate threats are all interlinked. Good examples of the effects of climate change are: global temperature rise, warming oceans shrinking ice sheets, glacial retreat, decreased snow cover, rise in sea level, declining arctic sea, ice ocean acidification, and desertification. This paper focuses on giving attention to decision makers on the seriousness of these risks and to point out how risk management and insurance techniques can help in the survival of their economies. Furthermore, it also opened avenues for universities to get involved in this research area.